Upaya pencegahan resistensi antibiotik melalui edukasi kesehatan di Puskesmas Siliwangi, Kabupaten Garut - Riansyah, Galih Hamdani; Tusliah, Lilis (KHIDMAH : Jurnal Pengabdian Masyarakat, 2025)
Antibiotic resistance poses a serious threat to the effectiveness of infection treatment, exacerbated by the high rate of non-prescription antibiotic use in Indonesia, which reaches 69%, along with low public awareness and weak regulatory control over drug distribution. This study aimed to evaluate the effectiveness of an interactive educational campaign in improving public knowledge about rational antibiotic use and the dangers of antibiotic resistance. The activity was conducted on April 26, 2025, at Puskesmas Siliwangi, Garut Regency, involving 40 participants who were accessing health services. The method used included an interactive presentation supported by leaflet media, and an evaluation was conducted using pre-test and post-test questionnaires containing five multiple-choice questions. Results showed an increase in the participants’ average score from 4.0 to 6.7, and 62.5% of participants achieved a score ≥7 out of a maximum of 10 after the session, indicating a significant improvement in understanding. A paired t-test revealed a statistically significant difference between pre- and post-intervention scores (t = 13.67; p < 0.05), demonstrating the effectiveness of the educational method applied. The discussion is grounded in the frameworks of Social Cognitive Theory, the Health Belief Model, and Constructivism, which explain how interactive and contextual learning approaches can enhance comprehension and shift participant perceptions regarding antibiotic use. In conclusion, the intervention was proven effective in increasing public awareness about antibiotic resistance and the importance of prudent antibiotic use. Similar activities should be conducted routinely in primary healthcare settings to support community-level antimicrobial resistance prevention efforts.